Arsitektur Organik pada Agrowisata The Lawu Park di Tawangmangu - Mara Injiela, Vidya Berlian; Paryoko, Vijar Galax Putra Jagat (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
Tourism development is one of the sectors that gets high priority because it increases the economy in Indonesia. As an agrarian country, agritourism is a potential destination because it utilizes agriculture and plantations as tourist attractions. This research takes a case study at The Lawu Park Agrotourism, Tawangmangu which is located in a highland area with natural environmental conditions. There is a diversity of activities designed to have interaction with the environment. This agro-tourism focuses on nature conservation in tourism objects by applying an organic architecture approach, which creates harmony between humans and nature. The purpose of this research is to find out more about the implementation of organic architecture in agritourism. This research uses a qualitative method with descriptive analysis to examine the eight basic concepts of organic architecture according to Frank Lloyd Wright in The Lawu Park Agrotourism. The results of the research obtained organic elements and special characters attached to the object of research. The resulting characteristics are in the form of open massing and resembling the environment, presenting natural elements, and making nature a part of the design.